Manajemen risiko industri minyak bumi dan gas pada proses industri dan manajemen risiko - Aulia Ikka Maharani; Almira Hana Aziza; Aisyah Fahira Lubis; Yulanda Tantra Zaharani (Environment Conflict, 2024)
The oil and gas industry is characterized by high-risk levels, necessitating integrated risk management. Risk control is achieved through a combination of engineering design, administrative measures, and the provision of personal protective equipment. Effective risk management implementation is crucial to ensuring workplace safety, preventing financial losses, and maintaining the sustainability of oil and gas industry operations. This research discusses risk management in the oil and gas industry. This industry poses various potential hazards that can have negative impacts, requiring integrated and systematic risk management. The objective of this research is to understand the processes in the oil and gas industry, potential hazards, and their risk controls. Literature review results indicate that the oil and gas industry process spans from exploration to the distribution of end products. Potential hazards include explosions and fires, confined space hazards, accident and collision hazards, entrapment hazards, and fall hazards. Risk control is conducted through risk identification and assessment based on probability and severity, followed by determining risk categories and recommended controls. Recommendations for risk control in this industry include the strict implementation of safety procedures, regular audits and inspections, adequate engineering design, safety training, and the effective use of personal protective equipment. With effective risk management, it is expected that the oil and gas industry can operate more safely and sustainably.